Introducing dialectical bases in defeasible argumentation - Capobianco, Marcela (1999)
Defeasible argumentation is a form of defeasible reasoning, that emphasizes the notion of an argument. An argument A for a conclusion q is a tentative piece of reasoning which supports q. In an argumentative framework, common sense reasoning can be modeled as a process in which we must determine whether an argument justifies its conclusion. The process mentioned aboye takes considerable computational effort. For this reason it would be convenient to keep a repository of already computed justifications to save work already done with previously solved queries. In this paper we introduce the concept of dialectical bases as a first step in direction to defining a justification maintenance system for argumentative frameworks.